Let C(n) be the constant term in the expansion of 

(x + 4)n.

 Prove by induction that 

C(n) = 4n

 for all n is in N.

(Induction on n.) The constant term of 

(x + 4)1

 is 

 = 4.



Suppose as inductive hypothesis that the constant term of 

(x + 4)k − 1

 is 

 

   for some 

k > 1.



Then (x + 4)k = (x + 4)k − 1 ·

image

  

 

 

image

 , so its constant term is 

 

  · 4 =  

 

  , as required.

in Other Math Topics by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

C(1)=4, so base case satsfies C(n)=4ⁿ when n=1.

Assume C(n)=4ⁿ. C(n+1)=(x+4)C(n)=xC(n)+4C(n)=xC(n)+4×4ⁿ. The constant in this expression is 4×4ⁿ=4ⁿ⁺¹.

But 4ⁿ⁺¹=C(n+1), which proves by induction that C(n)=4ⁿ for n∊ℕ.

by Top Rated User (660k points)

Related questions

Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
83,158 questions
87,989 answers
1,978 comments
4,883 users